2021
DOI: 10.1088/1361-665x/abeaeb
|View full text |Cite
|
Sign up to set email alerts
|

Remotely triggered morphing behavior of additively manufactured thermoset polymer-magnetic nanoparticle composite structures

Abstract: Shape memory polymers (SMPs) based systems find technological applications in diverse areas such as soft robotics, biomedical devices and aerospace structures. The shape memory (SM) response of a custom-made, additively manufactured (AM) SMP structure can be triggered by a remote, contactless AC magnetic field, resulting in morphing of the structure. We developed AM architectures based on SM thermoset polymers loaded with magnetic nanoparticles (MNPs). Composite structures were prepared from a crosslinkable po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The magnetic separation of biological material using particles was first applied in the 1970s to sorting cells [ 116 ] and, since then, “magnetophoresis”, as it has been termed, is widely used to separate specific cells from a biofluid or trim down cell populations ( Figure 7 ) [ 117 ]. The speed and ability to batch process biological samples make magnetic-activated cell sorting (MACS) an especially appealing option for cell sorting in flow cytometry instruments [ 117 ].…”
Section: Movementmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnetic separation of biological material using particles was first applied in the 1970s to sorting cells [ 116 ] and, since then, “magnetophoresis”, as it has been termed, is widely used to separate specific cells from a biofluid or trim down cell populations ( Figure 7 ) [ 117 ]. The speed and ability to batch process biological samples make magnetic-activated cell sorting (MACS) an especially appealing option for cell sorting in flow cytometry instruments [ 117 ].…”
Section: Movementmentioning
confidence: 99%
“…Such concepts may find applications in areas that range from wound care to dentistry [ 136 ]. Current trends focus on increasing the magnetic sensitivity of the embedded particles as well as exploring the wide space of combined chemical and mechanical activity [ 116 , 137 , 138 ].…”
Section: Movementmentioning
confidence: 99%
“…Moreover, they showed the morphing abilities of their composite material with flower-shaped and plane-shaped geometries that unfolded back to a flat position with the application of the magnetic field. Other soft robotic applications were envisioned by, for instance, Cohn et al, using their SMC of polycaprolactone dimethacrylate with 5 wt % of Fe 3 O 4 nanoparticles . In their published work, they showed the morphing of several structures when the material was subjected to a magnetic field (4 kA m –1 at 375 kHz) such as a self-deployable honeycomb cylinder or a spider web and the folding of a spiral.…”
Section: Applicationsmentioning
confidence: 99%
“…Other soft robotic applications were envisioned by, for instance, Cohn et al, using their SMC of polycaprolactone dimethacrylate with 5 wt % of Fe 3 O 4 nanoparticles. 167 In their published work, they showed the morphing of several structures when the material was subjected to a magnetic field (4 kA m –1 at 375 kHz) such as a self-deployable honeycomb cylinder or a spider web and the folding of a spiral. They investigated rolling and gripping movements using their SMC.…”
Section: Applicationsmentioning
confidence: 99%
“…Shape memory polymers (SMPs), as a smart material, [1][2][3][4][5][6] can obtain a temporary shape through some noncovalent interactions after removal of the external force and then recover to their permanent shape in response to external stimuli [7] (such as light, [8,9] heat, [10] electricity, [11] magnetism, [12,13] solvent, [14] etc.). Lendlein and Langer reported that SMPs may be used as self-tightening sutures for minimum invasive surgery in 2002, raising much interest for SMPs in biomedical applications.…”
Section: Introductionmentioning
confidence: 99%